2018
DOI: 10.1007/s00415-018-8783-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-to-date knowledge about the association between multiple sclerosis and the reactivation of human endogenous retrovirus infections

Abstract: Only three out of the 70 reviewed sources did not find provide evidence linking the reactivation of HERV and MS progression. On the other hand, overwhelming pieces of evidence confirm that the reactivations often drive the demyelinating plaques by initiating microglial inflammation. Pathological examinations reveal that the inflammatory monocytes (Ly6ChiCCR2 + CX3CR1lo) trigger the reactivation of the malignant T cells that are responsible for the progression of MS. These findings are promoting new discoveries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The findings would suggest that HERV activation might trigger a demyelination process, contributing to MS progression [97]. HERVs can be activated by several simuli, including viruses such as VZV, HSV-1, EBV and HHV-6 [98], however the most widely studied association is with EBV.…”
Section: Human Endogenous Retroviruses (Hervs)mentioning
confidence: 99%
“…The findings would suggest that HERV activation might trigger a demyelination process, contributing to MS progression [97]. HERVs can be activated by several simuli, including viruses such as VZV, HSV-1, EBV and HHV-6 [98], however the most widely studied association is with EBV.…”
Section: Human Endogenous Retroviruses (Hervs)mentioning
confidence: 99%
“…After Toll Like Receptor 4 (TLR 4) recognition, HERV-W env can activate innate immune response, especially macrophages and microglia, resulting in major inflammation [Arneth 2018;Bahrami 2018;Grandi 2018;Kremer et al 2019]. HERVs mostly leads to M1 macrophages stimulation, the proinflammatory phenotype; more than the antiinflammatory ones, M2 [Arneth 2018. M1 macrophages leads to reactive oxygen, nitrogen species and inflammatory cytokines release, and microglia cells also produce proinflammatory molecules [Kremer et al 2019].…”
Section: Hervmentioning
confidence: 99%
“…MS has several unique factors, such as its classical association with higher latitudes, intriguing pathology, women preponderance and a widely variety of clinical presentations [Lassman 2019;Kantarci 2019;Noubarksh 2019]. The disease has three phenotypes: Remittent Relapsing (RRMS), Primary Progressive (PPMS) and Secondary Progressive (SPMS) [Dobson 2018; Arneth 2018].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HERV expression is also increased in a number of other neurological (7,28,29) and non-neurological diseases, such as cancer (30). Furthermore, some think that HERVs may play beneficial roles in the pathophysiology of certain diseases (31); however, this may not be the case in all diseases as research on multiple sclerosis has suggested a pathogenic role for HERVs (32,33).…”
Section: Mechanismsmentioning
confidence: 99%